Pengembangan Strategi Kualitas Pelayanan Dalam Meningkatkan Kepuasan Pelanggan Pada Pabrik AMDK Abillaits Di Ambunten - Saifuddin Saifuddin; Laurentina Maria Husada (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This Bottled Drinking Water Factory (AMDK) is drinking water that is packaged and processed through electronic machines and is safe to drink. It is processed according to quality standards and in accordance with applicable techniques and meets the specified requirements so that bottled drinking water is safe for consumption by the public. This study aims to determine the service quality strategy carried out by the Abillaits AMDK factory in the Ambunten subdistrict, Sumenep Regency. Which was carried out using a qualitative approach method. Methods of data collection using observation, interviews, and documentation. With 1 key informant and 6 supporting informants. Data analysis techniques using data collection, data reduction, data presentation, and drawing conclusion. The results of research conducted at the Abillaits AMDK factory show 2 strategies implemented by the Abillaits AMDK factory in Ambunten in an effort to meet customer satisfaction, namely the basic and main strategy. Basic service strategies such as thanking customers, communicating with customers. Listening to customer complints and neat appearance. The main strategy is the services provided in accordance with SOP, fast and responsive, competitive advantage, building good relationships with customers, and timeliness.